A Narrative Review of Point of Care Ultrasound Assessment of the Optic Nerve in Emergency Medicine - Torey Lau; Justin S. Ahn; Rahim Manji; Daniel J. Kim (Life, 2023)
Point of care ultrasound (POCUS) of the optic nerve is easy to learn and has great diagnostic potential. Within emergency medicine, research has primarily focused on its use for the assessment of increased intracranial pressure, but many other applications exist, though the literature is heterogeneous and largely observational. This narrative review describes the principles of POCUS of the optic nerve including anatomy and scanning technique, as well as a summary of its best studied clinical applications of relevance in emergency medicine: increased intracranial pressure, idiopathic intracranial hypertension, optic neuritis, acute mountain sickness, and pediatric intracranial pressure assessment. In many of these applications, sonographic optic nerve sheath diameter (ONSD) has moderately high sensitivity and specificity, but the supporting studies are heterogeneous. Further studies should focus on standardization of the measurement of ONSD, establishment of consistent diagnostic thresholds for elevated intracranial pressure, and automation of ONSD measurement.